PERAN POLRI DALAM PEMBERANTASAN PERUSAKAN HUTAN - Anwar Sodik (UNISSULA, 2015)
The problem of forest destruction remains a national issue that requires serious attention from all sides. The necessity of the above gain serious attention is not due to the high forms of violation of forest destruction. Increased forest destruction related offenses easily known by the public not only through reports in the mass media, both print and electronic, but also from various data issued by various institutions, both private and government. Police as one of the institutions responsible for upholding the law must be prosecuted participation in supporting the realization of combating the destruction of forests. In connection with this, the problems that wish to reply to the author in this study about : How is the role of the police in combating forest destruction, efforts have been made by the police in the clearance of forest destruction, constraints What are occurring in the implementation combating forest destruction has been done by law enforcement officials Police in Perum Perhutani Forest Management Unit Kendal and alternative solutions to completion.This type of research used in this study is a normative legal research, with descriptive research normative specifications. The data source can be either secondary data and primary data, for the data collection method by means of literature study and interviews. Data analysis method used was qualitative analysis for this study starts from the existing regulations as the basis for positive law.From the results of this study concluded that: handling Combating Deforestation is not maximized and still piecemeal in handling, between the national police and Perum Perhutani still not fully synergies due to the absence of good cooperation with the team because the team is in the handling of forest destruction has not been working in groups , so as to enhance and maximize efforts should be made to develop cooperation component of the criminal Justice System (CJS) in order to create synergy between law enforcement officers in tackling crime forest destruction and laundering the proceeds of forest destruction and formed a team / joint task force of Perum Perhutani with the Police and given awards or rewards for their dedication in the disclosure of forest destruction that have been disturbing and detrimental to a country with immense loss.